Luna huye, huye. La mujer sefardí en el drama La informante (1983) de Paloma Díaz-Más - Paola Bellomi (Cuadernos AISPI)
Luna huye, huye. La mujer sefardí en el drama La informante (1983) de Paloma Díaz-Más